Development and Optimization of Transdermal System of Lisinopril dehydrate: Employing Permeation Enhancers: Transdermal system of lisinopril dehydrate - Jitendra Banweer,; A. K. Pathak,; Subhash Pandey, (Iranian Journal of Pharmaceutical Sciences, 2012)
Lisinopril dihydrate (angiotensin converting enzyme inhibitor) is a lysine derivative of enalaprilat and does not require hydrolysis to exert pharmacological activity. It has an extensive hepatic first pass metabolism resulting in a bioavailability of 6-60%. To overcome the poor bioavailability of the drug, transdermal patches have been prepared. The present study also aims at optimization of the formulation by incorporating the penetration enhancers in different concentration and ratios. The patches were prepared employing hydroxy propyl methyl cellulose (HPMC) and polyvinyl alcohol (PVA) in a 1:1 ratio as polymeric matrix using glycerol as plasticizer in 6% concentration. Binary solvent system (water-methanol) in a ratio of 70:30 was taken for the study. The transdermal devices were fabricated on glass substrate using solvent casting technique. Dimethylsulfoxide (DMSO) and propylene glycol (PG) were added as the penetration enhancers individually and in blends in different concentrations and ratios. Various physico-chemical evaluation parameters were carried over prepared patches to ascertain their integrity and physical stability at normal and accelerated temperature conditions. Optimization of the penetration enhancer’s concentration and ratio was done by performing in vitro diffusion rate studies using Keshary-Chein diffusion cell on Goatskin. The patch containing DMSO:PG in the ratio of 70:30, at 10% showed the best in vitro drug flux and possesses excellent physico-chemical properties at normal and accelerated temperature conditions. It could be concluded that all patches prepared increased the drug flux through skin but optimization of the formulation yields highest drug flux through patch containing DMSO and PG in 10 % concentration.